Continuous and flexible Renewable-Power-to-Methane via liquid CO2 energy storage: Revisiting the techno-economic potential. (January 2022) - Qi, Meng; Park, Jinwoo; Landon, Robert Stephen; Kim, Jeongdong; Liu, Yi; Moon, Il
Abstract: Power to Methane (PtM) processes directly coupled with renewables are limited by their ability to handle uncertainties caused by the intermittent nature of the power supply and fluctuations in gas demand as well as electricity prices. Continuous operation along with real-time scheduling is necessary to improve both their energy- and cost-efficiency. With the aim to enhance the PtM potential, a continuous and flexible renewable-PtM process is proposed using liquid CO2 energy storage (LCES) as a regulator to manage these uncertainties. To facilitate the integration of LCES with the PtM, a new LCES system has been designed, based on commercially available equipment, with an electrical round trip efficiency of 53.5%. The integrated process uses only water as a hot and cold utility and eliminates the storage of large volume flammable gas with both environmental and safety benefits. System-level process modeling and techno-economic analysis are performed based on 10 MW solid oxide electrolysis and catalytic methanation, in which the methane production costs are estimated with cost scenarios for today, 2030, and 2050. Results indicate the overall process yields an energy efficiency of 41.3%, and the methane produced from renewables will be cost-competitive with conventional routes in a future scenario via a flexible operational strategy assisted by the power grid and an expected low cost of solid oxide electrolyzer. The findings of this study clearly support that the flexible integration of the LCES with a PtM process to allow the latter's continuous operation, is a promising approach to make this technology economically viable. Highlights: Renewable-Power-to-Methane process uses CO2 energy storage for continuous production. Integrated process permits high-temperature electrolysis and eliminates hydrogen storage. Liquid CO2 energy storage helps to manage power supply and gas demand uncertainties. Flexible operation enables real-time planning and further cost reduction of the process. Methane produced by renewables will be cost-competitive with conventional routes.